Development of Multimedia Learning Geography Based on Adobe Flash to Increase Students’ Curiosity - Wahid Yuda Rejeki; M. Mukminan (Geosfera Indonesia, 2020)
This study aimed to analyze: (1) The needs of multimedia Adobe Flash-based towards geographic learning, (2) Geography multimedia learning of Adobe Flash-based to increase students' curiosity, and (3) The feasibility of utilizing geography multimedia based on Adobe Flash-based learning using ADDIE method. The needs of multimedia learning assessment data were collected through questionnaires towards respondents (2 teachers and 32 students). Meanwhile, regarding the feasibility of multimedia geography learning to increase students' curiosity, data were gathered both by tests and questionnaires. The feasibility assessment was performed with expert validation instruments and student assessments. The data analysis tool utilized was one-way ANOVA. The study results as follows: (1) Students needs of geography multimedia learning based on Adobe Flash, (2) For effectiveness rate of multimedia and treatment, Fcount = 20,875> Ftable = 3.99, indicates that geography learning based on Adobe Flash is can escalate students’ curiosity, (3) Based on experts judgments and the students’ assessments, it could be concluded that the geography multimedia learning based on Adobe Flash is 91.4%, hence it is very suitable to be implemented. Multimedia learning based on Adobe Flash geography has increased students' curiosity and feasible to implement. Keywords: Adobe Flash; Geography; Multimedia; Curiosity. Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License